Cadar dan Hukumnya: Bantahan Terhadap Penolakan Pensyariatannya - Muhammad Yusram; Azwar Iskandar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This study aimed to examine and explain the passages or propositions for the inquiry of veil use, some opinions of leading scholars, and to correct or refute some weak and controversial statements and interpretations related to veil and its law. This research employed qualitative-descriptive approach with content analysis technique and library research. The result shows that the veil is prescribed in Islam. This is based on the word of Allah in the Quran surah Al-Ahzab verse 59 which is interpreted by commentators among the companions and tabi'in as a command to cover the face. In the long story of ‘ifk, it is also mentioned that Aisyah covered her face. The scholars of schools (Hanafiyyah, Malikiyyah, Syafiiyyah, and Hanabilah), even though they disagree whether covering the face is obligatory or sunnah, they agree that veil is something recommended, specifically at the time when it is feared of triggering tribulation in society due to showing off the faces of women. Some commentators also hold that they must cover their faces as they emphasize in their commentaries. Some interpretations or statements related to veil as well as its law are weak. For example, the interpretation that the use of veil that prevailed in Arab societies was a tradition for certain societies is such a fallacious statement. Considering the existing history, the previous Arab communities which were commonly called the jahiliyyah community were ignorant about covering, let alone the veil.